A Review Study on Business Leaders’ Perspectives: Environmental Challenges and Climate Realities - Rajeev Sijariya; Nancy Khaira; Yogesh Sharma; Aditya Mishra (Journal of Advanced Research in Entrepreneurship, Innovation and SMES Management, 2026)
The Round Table cum Brainstorming Session on “Environmental Issues: Concerns of Business Leaders” was organised by the Atal Bihari Vajpayee School of Management & Entrepreneurship (ABVSME), Jawaharlal Nehru University, on 21st September 2023, under the aegis of the Indian Council of Social Science Research (ICSSR) project “Triple Bottom Line Approach for Resilient Recovery and Resurgence amid Covid-19: An Eco-Social Psychological Framework for Bharat 5.0 in the New Normal.” The session brought together a diverse group of stakeholders, including government representatives, policymakers, industry leaders, MSMEs, academicians, and research scholars. The objective was to 2 deliberate upon the increasing significance of environmental sustainability in business practices, identify barriers faced by industries in implementing pro-climate actions, and explore policy initiatives that could strengthen collaborative approaches. Key highlights included addresses by Members of Parliament, senior officials from the Ministry of MSME, industry associations, and academic experts, followed by a panel discussion with entrepreneurs and sustainability professionals. Findings emphasised the gap between awareness and behavioural change, financial and technological challenges faced by MSMEs, and the need for stronger policy support. The outcome was a set of actionable recommendations focusing on awareness building, incentives, collaborative partnerships, and innovation-driven strategies for sustainability.